The lawyer (Centaur Communications Group, 1987)
Presents "The Lawyer Online," a weekly newspaper for the legal profession. Includes current news articles and a database of past articles. Posts contact information via street address, fax number, and e-mail. Contains subscription information and letters to the editor. Offers access to feature articles and a job listings database, as well as advertising information.
Keywords: Law : Great Britain : Periodicals; Law; Droit des affaires; Great Britain; Electronic newspapers